2022
DOI: 10.3390/healthcare10112294
|View full text |Cite
|
Sign up to set email alerts
|

Reform of the Health Insurance Funding Model to Improve the Care of Noncommunicable Diseases Patients in Saudi Arabia

Abstract: Health insurance models are being considered as part of health system reforms in Saudi Arabia. This paper assesses the attributes of health funding models that support better control of non-communicable diseases (NCDs) and perspectives on health insurance as a model from the perspective of patients, clinicians, and managers. The study employed a mixed-methods research design that included quantitative and qualitative data gathering and analysis. Study findings indicated concerns that the current health funding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This could be attributed to the current reality of a universal healthcare model adopted in Saudi Arabia which provides free access to health services to all citizens [ 18 ]. However, this finding will likely change in the future, as the country shifts toward privatizing the health sector, thereby increasing the number of health insurance holders [ 19 ]. This issue is of great importance, as studies have identified a correlation between insurance status and health [ 20 ]; this is often reflected in patients in terms of the quality of services provided by their healthcare provider.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the current reality of a universal healthcare model adopted in Saudi Arabia which provides free access to health services to all citizens [ 18 ]. However, this finding will likely change in the future, as the country shifts toward privatizing the health sector, thereby increasing the number of health insurance holders [ 19 ]. This issue is of great importance, as studies have identified a correlation between insurance status and health [ 20 ]; this is often reflected in patients in terms of the quality of services provided by their healthcare provider.…”
Section: Discussionmentioning
confidence: 99%
“…30 Adopting personal health insurance coverage is seen to improve healthcare accessibility, reduce health inequities, enhance population health, and reduce government healthcare expenditures. 31 …”
Section: First Theme: Healthcare System Reformmentioning
confidence: 99%